Adnexal mass with extremely high levels of CA-125 and CA19-9 but normal Human Epididymis Protein 4 (HE4) and Risk of Ovarian Malignancy Algorithm (ROMA): Endometriosis or ovarian malignancy? A case report - Sepideh Khodaverdi; Soheila Amini-Moghaddam (Shahid Sadoughi University of Medical Sciences, 2018)
Abstract Background: It has been shown that Carbohydrate antigen (CA) 125 and CA 19-9 tumor markers are useful for diagnosis and follow up of ovarian carcinoma. Case: In this case, we reported the high level of CA-125 and CA 19-9 with large right ovarian intact endometrioma and extensive involvement of omentum. Conclusion: Human Epididymis protein (HE4) and Risk of ovarian malignancy algorithm (ROMA) can be useful in differentiation between malignancies and benign pathologies with a good sensitivity and specificity value